d / dx (ln (1-cosx / 1 + cosx) ^ 1/2)?

Antworten:

# cscx #.

Erläuterung:

Erinnere dich daran, # 1-cos2theta = 2sin ^ 2theta und (1 + cos2theta) = 2cos ^ 2theta #.

# :. y = ln ((1-cosx) / (1 + cosx)) ^ (1/2) #,

# = ln {(2sin ^ 2 (x / 2)) / (2cos ^ 2 (x / 2))} ^ (1/2) #,

# = ln (sin (x / 2) / cos (x / 2)) ............ (Stern ^ Stern) #,

#rArr y = lnsin (x / 2) -lncos (x / 2) #.

# :. dy / dx = d / dx {lnsin (x / 2)} - d / dx {lncos (x / 2)} ...... (Stern) #.

Hier bei der Kettenregel,

# d / dx {lnsin (x / 2)} = 1 / sin (x / 2) d / dx {sin (x / 2)} #,

# = 1 / sin (x / 2) * cos (x / 2) d / dx {x / 2} #,

#rArr d / dx {lnsin (x / 2)} = 1/2 * cos (x / 2) / sin (x / 2) ............. (Stern ^ 1) #.

Ähnlich, # d / dx {lncos (x / 2)} = - 1/2 * sin (x / 2) / cos (x / 2) ........ (Stern ^ 2) #.

Nutzen # (Stern ^ 1) und (Stern ^ 2) "in" (Stern), # wir haben,

# dy / dx = 1/2 {sin (x / 2) / cos (x / 2) - (- cos (x / 2) / sin (x / 2))} #,

# = {sin ^ 2 (x / 2) + cos ^ 2 (x / 2)} / {2sin (x / 2) cos (x / 2)} #,

# rArr dy / dx = 1 / sinx = cscx #.

Ein Liter :

Durch, # (Stern ^ Stern), y = lntan (x / 2) #.

# :. dy / dx = 1 / tan (x / 2) * d / dx {tan (x / 2)}, #

# = 1 / tan (x / 2) * sec ^ 2 (x / 2) * d / dx {x / 2}, #

# = cos (x / 2) / sin (x / 2) * sin ^ 2 (x / 2) / cos ^ 2 (x / 2) * 1/2 #,

# = 1 / (2sin (x / 2) cos (x / 2)) #.

# rArr dy / dx = cscx, # wie vorher!

Genießen Sie Mathe. Und verbreiten Sie die Freude!